Does Projection Artifact Removal Improve Visualization of Images in Optical Coherence Tomography Angiography?. (September 2019) - Juncal, Verena R.; Abadeh, Armin; Koushan, Keyvan; Berger, Alan R.; Chow, David R.
Purpose: This study assesses the frequency of projection artifacts in optical coherence tomography angiography (OCTA) en face images and compares images before and after applying a 3-dimensional projection artifact removal (3D-PAR) algorithm. Methods: This is a single-center, retrospective study that included consecutive patients with any underlying diagnosis who had OCTA obtained from January to March 2017. Patients with various retinal diseases and also healthy eyes were included. All participants underwent imaging with a scan area of 3 mm × 3 mm. The 4 default en face slabs were analyzed: superficial capillary plexus (SCP), deep capillary plexus (DCP), outer retina (OR), and choriocapillaris (CC). Images were qualitatively analyzed before and after 3D-PAR by 2 independent graders. Results: None of the SCP images had projection artifact before or after 3D-PAR. Scans of the DCP presented projection artifact in 96.5% of the cases. After 3D-PAR, 14.7% had a complete improvement of projection artifact, 56.5% had a partial improvement, 14.1% were worse, and 14.7% presented no change. In the OR, 2.9% had projection artifact, with a complete improvement after 3D-PAR in 40%, partial improvement in 20%, and no change in 40%. Projection artifact was initially present in 97.6% of the images in the CC. After 3D-PAR, there was a complete improvement in 72.9%, partial improvement in 26.5%, and no change in 0.6%. Choroidal neovascularization (CNV) was detected in 29 eyes (17.1%), and 3D-PAR improved detection of CNV in 12 cases (41.4%). Conclusions: OCTA with 3D-PAR technology minimizes the appearance of projection artifacts in the DCP and CC slabs.